The effect of credit risk and income diversification on financial sustainability with operational efficiency as a moderating - Erina Fitria Romadhoni; Achmad Farid Dedyansyah; Irma Indira (Universitas Nusa Cendana, 2026)
This research intends to investigate and assess the influence of credit risk and revenue diversification on the financial sustainability of banking businesses listed on the Indonesia Stock Exchange throughout the 2020–2024 period. The study applies a quantitative method with a descriptive approach. The population contains 47 banking companies, whereas the sample consists of 34 companies selected through purposive selection. Data analysis was carried out using SPSS version 24, applying multiple linear regression and Moderated Regression Analysis (MRA). The findings suggest that credit risk and income diversification positively influence financial sustainability. In contrast, operational efficiency has a detrimental influence on financial sustainability. Furthermore, operational efficiency, as a moderating variable, is found to have a significant negative moderating influence on the link between credit risk and financial sustainability, as well as between income diversification and financial sustainability. Keywords: Credit Risk; Operational Efficiency; Financial Sustainability; Income Diversification